Comparison of Energy Cost in Transfemoral Prosthesis Users using Mechanical Four-bar Linkage and Pneumatic System Prosthetic Knee Joints - Rahmi, Diah; Kristianto, Jusuf; Karma, Agusni (Journal of Prosthetics Orthotics and Science Technology, 2022)
Background. The prosthetic knee joint is an essential component of the transfemoral prosthesis. Different types of knee joints are used in transfemoral prosthesis. The different features found in artificial knee joints affecting on different energy costs to prosthesis user during walking. The selection of prosthetic knee joints should be appropriate to the user's needs. Research purposes. To analyze and comparing two types of prosthetic knee joint four bar linkage mechanical and pneumatic system in minimize the energy cost during walking. Research methods. Quantitative descriptive. The participants were 4 men transfemoral prosthesis user. Energy cost calculation is done with five minutes walking test, which is participants observed for 5 minutes by using prosthetic knee joint four bar linkages mechanical and pneumatic system. Results. The results showed that the prosthetic knee joint fourbar linkage pneumatic system decreased the energy cost by decreasing the value of PCI (p <0.05) and the participants's speed was increase significantly affected (p <0.05) compared to the fourbar linkage mechanical. Conclusion. The results show decreased PCI values and increased walking speed in the use of prosthetic knee joint fourbar linkage pneumatic system. It can be concluded that the use of pneumatic knee joints can clinically facilitate prosthesis users during walking.